Feasibility of a goal sharing digital platform designed to empower children with disability and their families: A qualitative, pre-implementation study - Meghan Wilson; Bridget O’Connor; Marnie Drake; Adam Scheinberg; Christine Imms; Rose Babic; Danny Hui; George Charalambous; Sarah Knight (Digital Health)
Background Family-centred goal setting is central to optimal care and outcomes for children with a disability. Digital innovations show promise for increased engagement and empowerment of families. While digital products have the potential to improve collaboration, there are barriers which may prevent service providers and families from using these resources. Objective This study aimed to: (a) understand goal sharing experiences of service providers and caregivers, and (b) identify views on a digital platform designed to share the goals of children with a disability between service providers and families. Methods Semi-structured interviews ( n  = 12) were conducted with paediatric service providers and caregivers in Australia. Transcripts were analysed using a qualitative content analysis approach. Findings Experiences of sharing goals were reflected in sub-categories: conversations and listening to families’ needs ; collaboration and building relationships ; adopting a family-driven approach ; big picture and specific goals ; communicating and documenting goals ; goals need to be meaningful; using a structured approach; National Disability Insurance Scheme (NDIS) goals and challenges and barriers . Views on using a digital platform were captured by sub-categories: potential to empower families ; collaboration and shared understanding; communication in your own time ; everything in the same place ; accessible and user friendly ; functionality and preferred features ; workload; some families might not engage with it and using new technology . Conclusion We developed an understanding of how the goals of children are shared and perspectives on a digital platform. These findings have implications for the development and implementation of digital health products designed to improve care for children with a disability.